2020
DOI: 10.1029/2019ea000667
|View full text |Cite
|
Sign up to set email alerts
|

Improving Convective Precipitation Forecasts Using Ensemble‐Based Background Error Covariance in 3DVAR Radar Assimilation System

Abstract: Skillful quantitative precipitation forecast using the numerical weather prediction model relies on an accurate estimate of the atmospheric state as an initial condition. Variational assimilation methods (VAR) have the potential to provide improved initial state estimation to the numerical weather prediction model using observations, prior data (background), and their respective error covariance. The quality of variational assimilation hinges on the background error statistics (BES) as it weights the error in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…EXP_CV5 and EXP_CV7 assimilate radar observations (both reflectivity and radial velocity) every 3 h from 0600 UTC to 1200 UTC, taking the analysis field assimilated at 1200 UTC as the initial field and integrating forward for 6 h. The difference is that the former uses the BE matrix of the CV5 scheme for assimilation, while the latter uses the BE matrix of the CV7 scheme for assimilation. Current studies generally agree that the BE matrix obtained statistically using the NMC method overestimates the characteristic length scale (Liu et al, 2005;Li et al, 2012;Sun et al, 2016;Stanesic et al, 2019;Thiruvengadam et al, 2020). Therefore, in the two assimilation experiments, the length scales are reduced to half of the default value, which are set to 0.5.…”
Section: Model Configuration and Experimental Designmentioning
confidence: 85%
“…EXP_CV5 and EXP_CV7 assimilate radar observations (both reflectivity and radial velocity) every 3 h from 0600 UTC to 1200 UTC, taking the analysis field assimilated at 1200 UTC as the initial field and integrating forward for 6 h. The difference is that the former uses the BE matrix of the CV5 scheme for assimilation, while the latter uses the BE matrix of the CV7 scheme for assimilation. Current studies generally agree that the BE matrix obtained statistically using the NMC method overestimates the characteristic length scale (Liu et al, 2005;Li et al, 2012;Sun et al, 2016;Stanesic et al, 2019;Thiruvengadam et al, 2020). Therefore, in the two assimilation experiments, the length scales are reduced to half of the default value, which are set to 0.5.…”
Section: Model Configuration and Experimental Designmentioning
confidence: 85%
“…The BES have a significant part in balancing and spreading of assimilated observation within a 3D-Var system. Thiruvengadam et al (2019;2020b) have found that control variables in BES have a significant role in increasing the precipitation forecast skill of a convective-scale 3D-Var radar assimilation system. The studies have further indicated that one of the crucial means for improving the convective precipitation forecast skill is through proper representation of BES within the 3D-Var framework.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various assimilation methods, three‐dimensional variational data assimilation (3D‐Var) is the usual approach in many operational and research centres (Courtier, 1998; Gauthier et al ., 1999; Lindskog et al ., 2004; Routray et al ., 2013; Maiello et al ., 2014; Mohanty and Gopalakrishnan, 2016) for assimilating DWR data due to its computational efficiency (Rabier, 2005). However, recent studies (Thiruvengadam et al ., 2019; 2020b) have shown the sensitivity of the 3D‐Var radar assimilation system to the structure of background error statistics (BES). The BES have a significant part in balancing and spreading of assimilated observation within a 3D‐Var system.…”
Section: Introductionmentioning
confidence: 99%